The Reality of Local Development in Libya under the Centralised Administration - Al-Sari, Malak Ezzedine; Wali, Taha Mohamed (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
The study aims to identify the reality of local development in Libya, clarify the relationship of the central authority with local administration concerning development, and identify the most important obstacles to local development. The study tries to examine the problem: that the application of the centralization system in the state was the reason behind the neglect of local development programs, and that achieving local development requires political will and the application of actual administrative decentralization. As for the methodology used in the study, the descriptive and analytical approach was used, and the study concluded that the success of the local development process in Libya requires giving a role to local administrations activating local government laws and transferring competencies to local authorities, providing the elements of political and economic stability and updating legislation related to local administration.
Keywords: Management; Development; Libya; Local; Central